ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI CRUDE PALM OIL (CPO) PT. PERKEBUNAN NUSANTARA VI (PERSERO) SOLOK SELATAN - Septian, Eka; Basri, Syafril; Pailis, Eka Armas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is purpose to know the influence of raw materials, labor, and machinery for the production of crude palm oil (CPO) and to know which are the most dominant factor of the production of crude palm oil (CPO) in PT. Perkebunan Nusantara VI south solok. This research used secondary data from monthly time series data of the month of October 2012-December 2014. Methods of analysis used in this research is quantitative descriptive method, partial and simultaneous analysis (multiple linear regression analysis with SPSS version 21.0. The results of test is simultaneous regression test (F test) showed that all independent variables studied had a significant effect on crude palm oil (CPO). Partial regression test (t test) showed that the variables of raw materials and machinery had a positive and significant effect on the variable production of crude palm oil (CPO). And the most dominant variable of production CPO PT. Perkebunan Nusantara VI south solok is machinery, technology intensive shows this industry. The magnitude of the effect that the ( by these three variables together against the dependent variables 88,1%, while the remaining 11% is influenced by other variables not examined in this research.Keywords: Production, raw materials, labor, machine, and Crude Palm Oil (CPO)